The traditional dairy value chain in Zambia and potential risk factors to microbiological food safety. (June 2021) - Phiri, Bruno S.J.; Sakumona, Mushekwa; Hang'ombe, Bernard M.; Fetsch, Alexandra; Schaarschmidt, Sara
Abstract: Milk is a highly valuable food for a balanced nutrition and contributes to food security in Sub-Saharan African countries like Zambia. The traditional dairy value chain accounts for a large share of Zambia's total milk supply. Comprehensive surveys yielding in around 400 filled-in questionnaires were carried out among traditional/smallholder farmers, milk collection centres (MCCs), informal traders, but also supermarkets/shops, and consumers in three Zambian provinces (Lusaka, Southern, Western). Using individual surveys for each stakeholder group, data were collected on general information and management practices, cattle disease management, hygienic measures, milk-handling practices, milk quality checks and backtracing, food safety knowledge, and milk consumption. The study provides insights into the traditional dairy chain and differences between the study provinces. For example, smallholder farms with high-yielding cattle breeds were dominating in the Lusaka Province, and here the MCCs received relatively large amounts of milk. In contrast, the surveyed farms in the Southern and Western Provinces were dominated by traditional cattle breeds, and the MCCs in the Western Province were the smallest. Distances for milk transport by farmers were largest in the Western Province, and here transport by foot was still common. Unrefrigerated storage and transport that favour proliferation of zoonotic agents in raw milk were frequently observed. Moreover, the survey uncovered hygiene deficiencies, particularly on farm level, for traders, and for consumers, which may further cause microbial contamination. Consumption of raw milk and products thereof was frequently identified and poses a health risk. Knowledge about food hygiene and safety needs to be improved along the Zambian dairy value chain. Highlights: In Zambia, milk is often consumed as raw milk (including traditional sour milk). The surveys indicate hygiene deficiencies along the traditional Zambian dairy chain. Correct handling of veterinary drugs and cooling of milk are further challenges. Knowledge on food safety appears to be low in the traditional Zambian dairy chain.